(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: One of the most important aspects of medicolegal injury examination is the determination of the age of the injury. This study of wound dating from the gross examination of abrasion is being conducted to look into the accuracy of dating the wounds by the age determined by gross changes with that of the time of infliction of injury. Methods: In this cross-sectional study, 102 dead bodies brought for medicolegal autopsy, having a well demarcated abrasion and a known time of infliction of injury were selected. Based on the duration of infliction, abrasions were categorized into 13 groups. Gross changes that follow blunt trauma were studied and correlated to the time frame of the occurrence of abrasion. Conclusion: A significant relationship between the age and color of abrasion (X2 72=387.59, P<0.001) was observed. On gross examination, bright red color was seen in abrasions aged <24 hours; reddish scabbed abrasion from 10 to 32 hours; brownish scabbed abrasion from 16.5 to 72.17 hours; dark brown scabbed abrasion from 35.5 to 157 hours; and black scabbed abrasion was observed only after 72 hours (3 days). Abrasions with scab fallen at a margin were seen from 7th to 14th days, and scabs completely falling off exposing hypopigmented skin were observed in abrasions aged >336 hours (>2 weeks).